"It is Nobbut (Only) an Oligarchy that Calls Itself a 'We'": Perceptions of journalism and journalists in Britain 1880–1900. (17th August 2016) - Conboy, Martin
Abstract : The period between 1880 and 1900 was rich with discussions of the role of both journalists and journalism in Britain. Not only did the period witness the intensification and systematization of technologies associated with the gathering and dissemination of news but it was also a time when journalists were beginning to identify themselves collectively and professionally. The technological developments and corresponding professional reassessment provided the periodicals of the time with a rich source of debate, disagreement and delineation regarding the function of journalism. While considering contemporary discussions of the social and political purposes of journalism, we should be aware that definitional problems have beset the practice for well over a hundred years and across very different technological and cultural regimes. This paper explores a range of periodical discussion with the intention of highlighting key points in the debate from the late nineteenth century and asserts the continuing relevance of defining the roles of journalism in the present day.